2020
DOI: 10.1002/biot.201900217
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Analysis of Tissue Spheroids Fabricated from Different Types of Cells

Abstract: Reproducible, scalable, and cost effective fabrication and versatile characterization of tissue spheroids (TS) is highly demanded by 3D bioprinting and drug discovery. Consistent geometry, defined mechanical properties, optimal viability, appropriate extracellular matrix/cell organization are required for cell aggregates aimed for application in these fields. A straightforward procedure for fabrication and systematic multiparametric characterization of TS with defined properties and uniform predictable geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 73 publications
(75 reference statements)
2
20
0
Order By: Relevance
“…While microcarriers offer a relatively simple solution to the problem of how to expand mammalian cells at scale with minimal space requirements, they may also introduce limitations related to the cost of cell dissociation and separation, the cost of the microcarriers themselves, maximum cell densities that can be achieved, and potential impacts on the nutritional and/or organoleptic properties of the final product. Alternative strategies based on spheroids, [ 180 , 181 , 182 , 183 ] organoids, [ 184 ] or adaptation to single‐cell suspension culture [ 185 ] may obviate the need for microcarriers. At this point, it is unclear which of these strategies may prove most effective at producing high‐quality CM products at a sufficiently low cost.…”
Section: The Basic Scaffold Typesmentioning
confidence: 99%
“…While microcarriers offer a relatively simple solution to the problem of how to expand mammalian cells at scale with minimal space requirements, they may also introduce limitations related to the cost of cell dissociation and separation, the cost of the microcarriers themselves, maximum cell densities that can be achieved, and potential impacts on the nutritional and/or organoleptic properties of the final product. Alternative strategies based on spheroids, [ 180 , 181 , 182 , 183 ] organoids, [ 184 ] or adaptation to single‐cell suspension culture [ 185 ] may obviate the need for microcarriers. At this point, it is unclear which of these strategies may prove most effective at producing high‐quality CM products at a sufficiently low cost.…”
Section: The Basic Scaffold Typesmentioning
confidence: 99%
“…The high magnification and resolution of the electron microscope (scanning or transmission) allows high-resolution images of 3D spheroids (nanoscale). Tissue morphology can be observed more clearly by SEM, which is often used for MTS observation (Costa et al 2019;Kelm et al 2003;Koudan et al 2020). Koudan et al used different types of cells to construct tissue spheroids (TSs), and images of SEM showed that TSs would retain specific tissue structures, such as vesicles and microvilli (Koudan et al 2020).…”
Section: Microscopymentioning
confidence: 99%
“…Tissue morphology can be observed more clearly by SEM, which is often used for MTS observation (Costa et al 2019;Kelm et al 2003;Koudan et al 2020). Koudan et al used different types of cells to construct tissue spheroids (TSs), and images of SEM showed that TSs would retain specific tissue structures, such as vesicles and microvilli (Koudan et al 2020). Lee et al used AIS 1800C electron microscope to perform SEM analysis of A549 MTSs at different magnifications and found that MTSs has microvilli in the outer layer (Lee et al 2019).…”
Section: Microscopymentioning
confidence: 99%
“…[11][12][13] As a result of these processes, the elasticity of breast tumors rises values up to 100 kPa (measured as Young's moduli), [6] differing to those analyzed in healthy tissues (up to 4.0 kPa, measured as Young's moduli) [6,14] or spheroids (up to 6.0 kPa, measured as Young's moduli). [9,15] Thus, the use of the alginate-gelatin blend was chosen due to its biophysical similitudes to tumor tissues. While gelatin allows cell-matrix anchorage and matrix degradation, nonbiodegradable alginate aims to keep the scaffold morphology, increasing simultaneously the mechanical stress upon confined cells.…”
mentioning
confidence: 99%